DETERMINAN PRODUKSI AYAM BROILER DI KOTA KUALA PEMBUANG KABUPATEN SERUYAN - Lili Winarti; Rokhman Permadi (Lampung University, 2022)
Our sub-sector is the sector that not only plays a role as a producer of meat for the community, but also has an important role in the development of the agricultural sector in general and in the development of livestock. Increasing population and production does not always represent a large profit or income for businesses. In broiler farming, there are several factors that are often faced by breeders, including broiler breeders in Kuala Pembuang City, Seruyan Regency. Uncertain availability and fluctuations in the price of production factors are serious problems that are always faced by farmers. The purpose of this study was to analyze the determinants of broiler production in Kuala Pembuang. This research was carried out from February to July 2021, starting from preparation, data analysis to report preparation. In this study, the population was broiler breeders in the city of Kuala Pembuang, especially in Seruyan Hilir and Seruyan Hilir Timur subdistricts, which collected 27 broiler breeders who were actively running a business. Data collection technique uses the census method and data processing uses linear regression analysis method with the help of Eviews 7 software. Based on the research, it was obtained: The significant determinants of broiler chicken production in Kuala Pembuang City were DOC and cages, where the DOC had a positive effect on production, while the cage had a negative effect on broiler production, and the insignificant determinants on broiler chicken production were feed, medicines, and labor use (TKDK and TKLK).Key words: Broiler Chicken, Determinants, Production.